Social prescribing: Exploring general practitioners' and healthcare professionals' perceptions of, and engagement with, the NHS model. (23rd July 2022) - Moore, Coco; Unwin, Peter; Evans, Nick; Howie, Frances
Abstract: Social prescribing (SP) has rapidly expanded over recent years. Previously a bottom‐up, community‐led phenomenon, SP is now a formal part of structured NHS policy and practice. This study was designed to ascertain how general practitioners and other primary healthcare professionals (HCPs) within one clinical commissioning group (CCG) perceive and engage with this new NHS model. The research comprised an online survey distributed to HCPs within a predominately rural, English CCG between June and August 2021. Qualitative data were gathered and analysed using reflexive thematic analysis. Positive portrayals of SP were found, although definitions and perceptions varied greatly. Many HCPs reported high levels of engagement with SP services; yet referral rates appeared to remain significantly lower than the previously estimated 20% of primary care attendees referred for social reasons. Moreover, 96% of HCPs reported signposting patients directly to community or external services, rather than referring them to SP. This signposting, which has been positioned as a model of SP, reflects engagement with SP in practice, which is likely to have pre‐dated the introduction of the fuller NHS model. HCPs may be unaware that this could be classed as a social prescription, and this type of SP remains uncaptured within NHS statistics. These results indicate an underuse of the national system set up to deliver one particular model of SP, rather than that SP does not occur. Additionally, despite national guidance issued to accompany the NHS model, practices such as referral and feedback processes, and link worker presence within practices, were not uniform even within this single CCG. Nevertheless, understanding is increasing as SP becomes embedded within primary care. The lack of consistency in referrals between practices warrants further examination in terms of equity of service choices to patients, as does the very low self‐reported referral rate to SP.